Evaluasi Kinerja Penerapan Zona Selamat Sekolah (ZOSS) dI SD Negeri 21 Kota Pekanbaru - Hamam Baihaqi, Fadillah; Lubis, Fadrizal; Anggraini*, Muthia (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2024)
Many school facilities in big cities are located on the side of highways, where many vehicles travel at high speeds, thereby endangering children when crossing. The research aims to determine how effective the use of ZoSS is at SD Negeri 21 Pekanbaru. The method used is data analysis using the normal distribution statistic Z test. The research results show that in terms of markings and signs there are still many that are missing, some of the markings have faded. The level of service on the Pahlawan Kerja road is included in category D. The average instantaneous vehicle speed on the Pahlawan Kerja road is 40.46 km/hour, which means it still exceeds the permitted speed. The behavior of students at SD Negeri 21 Pekanbaru with a calculation result of -0.95 is still classified as not safe with a permissible error rate of 1.645. For the introductory behavior of students at SD Negeri 21 Pekanbaru it is classified as safe with a calculation result of 13.85 which is greater than the permitted error level. 1,645. The conclusion from the data that has been studied shows that the effectiveness of using ZoSS on the Job Hero road has not been effective. The suggestion regarding this problem is that there should be maintenance and additional traffic signs needed to complete the ZoSS facilities and training from the police for crossing guides so that the safety of students at SD Negeri 21 Pekanbaru is maintained.